2006
DOI: 10.1088/0741-3335/48/4/002
|View full text |Cite
|
Sign up to set email alerts
|

Phase speed of electrostatic waves: the critical parameter for efficient electron surfing acceleration

Abstract: Particle acceleration by means of non-linear plasma wave interactions is of great topical interest. Accordingly, in this paper we focus on the electron surfing process. Self-consistent kinetic simulations, using both relativistic Vlasov and PIC (Particle In Cell) approaches, show here that electrons can be accelerated to highly relativistic energies (up to 100mec 2 ) if the phase speed of the electrostatic wave is mildly relativistic (0.6c to 0.9c for the magnetic field strengths considered). The acceleration … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…This is a consequence of the sideband and coalescence instabilities, that limit the life-time of the saturated ES wave. For relativistic proton beam speeds, however, the ES waves stabilize [64], resulting in efficient electron surfing acceleration [44]. The stability of the ES waves is demonstrated by figure 3, which shows the modulus of the ES wave fields that are driven by two counterpropagating proton beams.…”
Section: The Mildly Relativistic Two-stream Instability In Magnetized...mentioning
confidence: 97%
See 1 more Smart Citation
“…This is a consequence of the sideband and coalescence instabilities, that limit the life-time of the saturated ES wave. For relativistic proton beam speeds, however, the ES waves stabilize [64], resulting in efficient electron surfing acceleration [44]. The stability of the ES waves is demonstrated by figure 3, which shows the modulus of the ES wave fields that are driven by two counterpropagating proton beams.…”
Section: The Mildly Relativistic Two-stream Instability In Magnetized...mentioning
confidence: 97%
“…We demonstrate how a shock and the shock-reflected ion beam form, if two plasma slabs collide at a superAlfvenic speed perpendicularly to the ambient magnetic field. We discuss the interaction of the shock-reflected proton beam with the upstream plasma [32,33,[39][40][41][42][43] and, in particular, we demonstrate that electrons can be accelerated to high energies by two-stream instabilities and wakefield acceleration and that they can develop power law distributions due to their interaction with an ambient magnetic field [44] in section 3 and electrostatic (ES) turbulence [45][46][47] in section 4. Such processes can exist in the presence of a strong guiding magnetic field, a high plasma temperature and a moderately relativistic flow speed, since then the competing relativistic Weibel instability is suppressed [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Early in 1983, Dawson et al [14,15] showed electrons can be accelerated when they are trapped in EPWs propagating perpendicular to a magnetic field, and meanwhile the EPWs heavily damped. The use of transverse external magnetic fields in plasma has been extensively studied in particle acceleration [16,17], but there are only a few studies [18] on the nonlinear damping mechanism. Winjum et al [19] showed that, in the kinetic regime, a transverse magnetic field with tens of tesla can significantly reduce backward stimulated Raman scattering (BSRS) reflectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we suggest that at least some of the features of early afterglows can be related to complex shock physics and/or features in the fireball/jet. In fact, simulations of the acceleration of electrons and positrons by the first and second Fermi processes show that the evolution of electric and magnetic fields as well as the energy distribution of accelerated particles are quite complex (Bednarz & Ostrowski 1996; Dieckmann et al 2006; Rieger, Bosch‐Ramon & Duffy 2007). Plasma instabilities lead to the formation of coherent electric and magnetic fields and acceleration of particles (Yang, Arnos & Langdon 1994; Silva et al 2002; Wiersma & Achterberg 2004; Reville, Kirk & Duffy 2006).…”
Section: Introductionmentioning
confidence: 99%